2007
DOI: 10.1063/1.2771535
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitric oxide on gain and output power of a non-self-sustained electric discharge pumped oxygen-iodine laser

Abstract: This letter discusses the effect of nitric oxide on gain and output power of a pulser-sustainer discharge excited oxygen iodine laser. Adding small amounts of NO to the laser mixture ͑a few hundreds of ppm͒ considerably increases gain and output power due to ͑i͒ O atom titration and resultant slower I * atom quenching and ͑ii͒ improved stability of the dc sustainer discharge, which allows stable operation at significantly higher discharge powers. Gain on the 1315 nm iodine atom transition and laser power in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2

Year Published

2008
2008
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 11 publications
1
27
2
Order By: Relevance
“…However, the complexity and weight of the chemical generators required for high-power operation pose problems for field deployment [3]. Consequently, there has been a long standing interest in the possibility of developing a discharge driven laser (DOIL) where O 2 (a 1 D) is produced via an electric or microwave discharge [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the complexity and weight of the chemical generators required for high-power operation pose problems for field deployment [3]. Consequently, there has been a long standing interest in the possibility of developing a discharge driven laser (DOIL) where O 2 (a 1 D) is produced via an electric or microwave discharge [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The initial thinking was that NO, which is easily ionized, would help to reduce the ratio. In practice it was found that the addition of small flows of NO had a minor effect on the discharge voltage, but greatly improved the O (a) yield [12,16,28,29]. This effect has been partly attributed to the removal of O atoms by the sequence (12) (13) Oxygen atoms in the discharge lead to the undesirable formation of O , and this chemistry is also suppressed by the addition of NO.…”
Section: The Role Of Atomic Oxygen In Doilmentioning
confidence: 99%
“…Three different groups have investigated DOIL's that employ pulser-sustainer discharges [29,34,[45][46][47][48][49][50][51][52][53]. This approach permits the application of non-self sustained discharges with low ratios.…”
Section: Recent Advances In Doil Developmentmentioning
confidence: 99%
See 2 more Smart Citations